VARIABILITY AND CORRELATION STUDY OF SOME ADVANCED LINES OF Brassica rapa (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Variability, heritability, genetic advance and correlation were assessed in eleven advanced lines of Brassica rapa obtained through inter-varietal crosses along with three popular check varieties at the experimental field of Sher-e-Bangla Agricultural University. Significant variations were found in yield per hectare and all the yield components that were taken under the study. Highest yield per hectare (2111.33 kg) was found in SAUSR 14 (TORI-7×BARI Sarisha-9). The advanced line SAUSR 08 (BARI Sarisha-6×TORI-7) matured early (83.67 days) and produced moderate yield (1662.00 kg). It could be assumed from the mean performance that SAUSR 14 and SAUSR 08 showed better performance over the popular check varieties in respect of yield and maturity. Highest GCV (20.06%) and PCV (31.71%) were observed in number of siliquae per plant. Genotypic variance was lower than phenotypic variance for all characters except yield per hectare. High heritability in broad sense (91.14% and 79.25%) was observed for days to 50% flowering and days to 80% flowering. Highest genetic advance (36.56%) was found for number of siliquae per plant. Low heritability (29.27%) with high genetic advance (23.14%) was observed for yield per hectare. Highly positive significant phenotypic correlation with yield per hectare was seen in days to 80% maturity and number of secondary branches per plant. Days to 50% flowering and siliquae length showed negative highly significant phenotypic correlation with the yield per hectare